2018
DOI: 10.1186/s12872-018-0802-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of clinical outcome in patients treated with cardiac resynchronization therapy - the role of NT-ProBNP and a combined response score

Abstract: BackgroundCardiac resynchronization therapy (CRT) is an established therapy for appropriately selected patients with heart failure. Response to CRT has been heterogeneously defined using both clinical and echocardiographic measures, with poor correlation between the two.MethodsThe study cohort was comprised of 202 CRT-treated patients and CRT response was defined at 6 months post-implant. Echocardiographic response (E+) was defined as a reduction in LVESV ≥ 15%, clinical response as an improvement of ≥ 1 NYHA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
(41 reference statements)
2
12
0
1
Order By: Relevance
“…It is known that inflammation plays an important role in the As a marker of ventricle dysfunction, the plasma NT pro-BNP level is a comprehensive index of cardiac function with high sensitivity and specificity. Similarly, in our study, elevated NT pro-BNP levels were an independent predictor of HF progression and mortality, which is consistent with several earlier studies [16,29,30].…”
Section: Variables Associated With the Risk Of All-cause Mortality Ansupporting
confidence: 94%
See 2 more Smart Citations
“…It is known that inflammation plays an important role in the As a marker of ventricle dysfunction, the plasma NT pro-BNP level is a comprehensive index of cardiac function with high sensitivity and specificity. Similarly, in our study, elevated NT pro-BNP levels were an independent predictor of HF progression and mortality, which is consistent with several earlier studies [16,29,30].…”
Section: Variables Associated With the Risk Of All-cause Mortality Ansupporting
confidence: 94%
“…Over the past decades, prior risk models [9, 10, [14][15][16] were derived with good calibration and accuracy in derivation cohorts or Western validation cohorts; however, Asian populations, especially The prevalence of ischemic HF in CRT candidates was greater than 50% in most studies [1,7,9,10,18] conducted in North America and Europe. However, the situation in Asia is significantly different with regards to the subtype of CRT candidates [19][20][21].…”
Section: The Published Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevation of these peptides has a well established role for prediction of mortality for both acute and chronic heart failure situations [16][17]. Bakos Z et al [18] found that BNP levels were significantly reduced in CRT responders compared to non-responders, and that the greatest reduction was seen in those patients who exhibited both a clinical and echocardiographic positive response. In contrast, patients with no BNP reduction had a poor prognosis with significantly higher mortality and heart failure hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, prior risk models [9,10,[14][15][16] were derived with good calibration and accuracy in derivation cohorts or Western validation cohorts; however, Asian populations, especially Chinese participants, are rarely used for validation [17]. VALID-CRT [11]and sex category, renal function, ECG/QRS width, ejection fraction, and NYHA class (ScREEN) [8] scores were derived and validated in European multicenter studies, and ejection fraction, atrial fibrillation, age, renal function, and NYHA class (EARRN) [10] does not have a validation population.…”
Section: The Published Scoresmentioning
confidence: 99%